The increasing prevalence of CPV-2c in domestic dogs in China - Hao, Xiangqi; He, Yuwei; Wang, Chuhan; Xiao, Weiqi; Liu, Ruohan; Xiao, Xiangyu; Zhou, Pei; Li, Shoujun (PeerJ, 2020)
Background Canine parvovirus type 2 (CPV-2), a serious pathogen, leads to high morbidity and mortality in dogs and several wild carnivore species. Although it is a DNA virus, it evolves particularly rapidly, with a genomic substitution rate of approximately 10−4 substitutions/site/year, close to that of some RNA viruses. Tracing the prevalence of CPV-2 in dogs is significant. Methods In this study, an aetiological survey was carried out from 2016 to 2019 in Guangdong Province, China, involving Guangzhou, Shenzhen and Dongguan. Furthermore, to systematically analyse the prevalence of CPV-2 in China, the VP2 gene sequences of all Chinese isolates were downloaded from the NCBI nucleotide database in December 2019, and changes in CPV-2 variants were examined. Results A total of 55.7% (34/61) of samples were CPV-2 positive by PCR detection and virus isolation. In addition to different variants circulating in dogs, coinfection with multiple variants was identified, as was coinfection with other canine enteric pathogens in some cases. Two previously reported amino acid sites, A5G and Q370R of CPV-2c mutants, reported in variants in China were assessed, and several CPV-2 isolates with P13S and K582N mutations were detected in this study. Finally, we speculate on the prevalence of different CPV-2 variants in China. According to the VP2 gene sequence obtained from the NCBI nucleotide database, the proportion of different variants in China has changed, and CPV-2c appears to be growing rapidly. In conclusion, this aetiology survey suggests that CPV-2 continues to be common in China and that the prevalence of CPV-2c is increasing.
Keywords: CPV-2c; VP2; Aetiological survey; Prevalence